‘URF DAN PENGARUHNYA DALAM PENETAPAN HUKUM ISLAM - Ujang Ruhyat Syamsoni (Program Studi Hukum Keluarga Islam, Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2025)
The Arabs, as the nation to whom the Prophet Muhammad (peace be upon him) was sent and upon whom the Qur’an was revealed, were not a people devoid of traditions and culture. Pre-Islamic Arab society had already developed a distinctive culture and way of life deeply embedded within their daily existence. The mission of the Prophet Muhammad, with the message revealed by Allah, was intended to perfect the morality (akhlaq) of the Arabs in particular and humankind in general. Morality in both Arab and non-Arab societies was manifested in habitual practices that had long been entrenched in the fabric of life. Naturally, the customs of one society differ from those of another. Given these differences, Islamic law must be capable of accommodating the traditions and practices of various communities so that it can be embraced universally by all people, regardless of language, race, skin color, or ethnicity. The process of accommodating, acculturating, and assimilating societal customs into Islamic law is known as ʿurf. The customs (ʿurf) of a community may be accepted in their entirety, accepted with necessary modifications, or rejected altogether when they contradict Islamic law, with consideration given to the principles of maslahah (benefit) and mafsadah (harm) underlying such practices.